2017
DOI: 10.18632/oncotarget.14920
|View full text |Cite
|
Sign up to set email alerts
|

The HOTAIR, PRNCR1 and POLR2E polymorphisms are associated with cancer risk: a meta-analysis

Abstract: Long non-coding RNAs (LncRNAs) have been widely studied and aberrant expression of lncRNAs are involved in diverse cancers. Genetic variation in lncRNAs can influence the lncRNAs expression and function. At present, there are many studies to investigate the association between lncRNAs polymorphisms and cancer susceptibility. However, it has no systematic study to evaluate the association. We performed a meta-analysis to summarize the results of common lncRNAs (HOTAIR, PRNCR1, POLR2E and H19) polymorphisms on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 46 publications
1
29
1
Order By: Relevance
“…In a meta-analysis performed by Chu et al (34), the rs1016343 and rs16901946 variants of PRNCR1 were found to significantly increase the risk of cancer; however, their findings did not support a significant association of the rs13252298, rs7007694 and rs1456315 polymorphisms with cancer risk. Another meta-analysis conducted by Lv et al (35) also revealed that two polymorphisms (rs1016343 and rs16901946) of PRNCR1 were associated with increased cancer risk.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a meta-analysis performed by Chu et al (34), the rs1016343 and rs16901946 variants of PRNCR1 were found to significantly increase the risk of cancer; however, their findings did not support a significant association of the rs13252298, rs7007694 and rs1456315 polymorphisms with cancer risk. Another meta-analysis conducted by Lv et al (35) also revealed that two polymorphisms (rs1016343 and rs16901946) of PRNCR1 were associated with increased cancer risk.…”
Section: Discussionmentioning
confidence: 90%
“…Association between genetic polymorphisms of long non-coding RNA PRNCR1 and prostate cancer risk in a sample of the Iranian population PRNCR1 variants that were identified as potential risk factors for cancer were selected (26,(28)(29)(30)34,35). Genetic risk factors for cancer may vary among diverse populations.…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis performed by Chu et al 24 revealed that HOTAIR rs920778 variant increases susceptibility to cancer. Their findings did not support an association between rs1899663 and rs4759314 variants and the risk of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…One of which is an antisense noncoding RNA in the INK4 locus ( ANRIL ), one is highly upregulated in liver cancer ( HULC ), one is a poly (ADP‐ribose) polymerase‐1 ( PARP1 ), and one is a RNA polymerase II polypeptise E gene ( POLR2E ). Chu et al concluded that POLR2E rs3787016 contributes to cancer risk by conducting a meta‐analysis; however, glioma was not included in the study. In addition, Wang et al demonstrated that HULC SNPs (rs1041279 and rs2038540) might enhance hepatocellular cancer risk, whereas they are not associated with overall survival.…”
Section: Introductionmentioning
confidence: 99%